Comparative Analysis of Teams Game Tournament (TGT) and Genius Learning Models in Enhancing Islamic Understanding in the Digital Era - Apriyani, Hikma; Fatoni, Ilham; Syafe’i, Imam; Hadiati, Eti; Rahmatika, Ratu Vina (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This research aims to determine the effectiveness of the Teams Game Tournament (TGT) and Genius Learning models in Islamic Religious Education (PAI) learning in the digital era. Two groups of students were tested with the TGT model, and two others were tested with the Genius Learning model. The instruments used included comprehension tests, observations, and questionnaires about learning motivation. Data were analyzed using statistical tests. The research results show that both learning models improve students' understanding of Islam. The TGT model is more effective in enhancing cognitive and collaborative aspects, while Genius Learning is better at creating enjoyable learning experiences and improving the retention of PAI material. The statistical test results showed a significant difference between the two models (p < 0.05). Integrating technology in both models makes learning more relevant to the student's environment.In conclusion, both learning models can enhance students' understanding of Islam in the digital era. The TGT model excels in cognitive and collaborative aspects, while Genius Learning is more effective in enhancing material retention. Combining collaborative approaches and enjoyable learning experiences can overcome learning difficulties in the digital era.